2009
DOI: 10.1111/j.1365-2044.2009.06126.x
|View full text |Cite|
|
Sign up to set email alerts
|

Atomised lidocaine for airway topical anaesthesia in the morbidly obese: 1% compared with 2%*

Abstract: SummaryAirway anaesthesia using atomised lidocaine for awake oral fibreoptic intubation in morbidly obese patients was evaluated using two doses of local anaesthetic. In this randomised, blinded prospective study, 40 ml of atomised 1% (n = 11) or 2% (n = 10) lidocaine was administered with high oxygen flow as carrier. Outcomes included time for intubation, patient tolerance to airway manipulation, haemodynamic parameters, the bronchoscopist's overall satisfaction, and serial serum lidocaine concentrations. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Care should be taken when using these agents, however, because of delays in postoperative awakening and the occurrence of complications associated with a decline in cardiac function. Lidocaine as an airway topical anesthetic is widely used to attenuate hemodynamic reflexes [3,17,18,25,2731]. Godzieba et al indicated that use high dose or high concentration of lidocaine (≤4 ampules) with epinephrine seems to be relatively safe for cardiovascularly compromised patients [51].…”
Section: Discussionmentioning
confidence: 99%
“…Care should be taken when using these agents, however, because of delays in postoperative awakening and the occurrence of complications associated with a decline in cardiac function. Lidocaine as an airway topical anesthetic is widely used to attenuate hemodynamic reflexes [3,17,18,25,2731]. Godzieba et al indicated that use high dose or high concentration of lidocaine (≤4 ampules) with epinephrine seems to be relatively safe for cardiovascularly compromised patients [51].…”
Section: Discussionmentioning
confidence: 99%
“…The most appropriate concentration of atomised lignocaine is 2%, allowing better patient response and higher operator satisfaction compared to 1% lignocaine [28] and resulting in a smaller drug dosage and lower plasma concentrations compared with 4% [26]. Combining nebulization (lignocaine 4% 200 mg) and 'spray-as-yougo' (without sedation) produces good FOI conditions and patient comfort [24].…”
Section: Airway Topicalizationmentioning
confidence: 99%
“…The smallest force of 3.9 N showed the lidocaine crossing over the toxic plasma level of lidocaine (5 µg/ml) at a time of nearly one hour. Usually a range of 5 to 10 µg/ml is considered to be a toxic concentration for lidocaine in blood plasma [55].…”
Section: Vertical Percutaneous Lidocaine Permeationmentioning
confidence: 99%